FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECACINGAN PADA ANAK SD - Brema Perangin-angin, Frans; R.D. Sitorus, Esther; Lumongga , Fitriani (Jurnal Kedokteran Methodist, 2021)
Background: Helminthiasis or helminthiasis is a disease that belongs to neglected disease, which is a disease that is less concerned in the community and the incidence of diseases is chronic. Frequent helminthiasis infections are Soil-Transmitted Helminths (STH) which are infections of intestinal worms transmitted through the soil. In Indonesia itself helminthiasis still a health problem that occurs in the community with the frequency of incidence rate helminthiasis 2.5%-62%. The high incidence of helminthiasis is caused by factors such as environmental sanitation, poor self-cleanliness, low socio-economic and geographical State. This research aims to determine the factors related to the occurrence of Helminthiasis in elementary school students. Methods: This study uses the method of literature review or literature review. The data collected is in the form of scientific journals that have been published in online journals, both nationally and internationally. The number of journals analyzed was 15 (fifteen) journals Conclusion: There is a relationship between the habit of not washing hands, not keeping nails clean and the habit of often playing on the ground with the incidence of worms in elementary school children. The factor of not washing hands before eating, is the most dominant cause of helminthiasis experienced by elementary school children.